Hsp70 plasma membrane expression on primary tumor biopsy material and bone marrow of leukemic patients - Hantschel, Markus (Cell Stress Society International, 2000)
A tumor-selective cell surface localization of heat shock protein 70 (Hsp70), the major heat-inducible member of the Hsp70 group, correlates with an increased sensitivity to lysis mediated by human natural killer (NK) cells and, therefore, might be of clinical relevance. With the exception of mammary carcinomas, an Hsp70 plasma membrane expression was found on freshly isolated human biopsy material of colorectal, lung, neuronal, and pancreas carcinomas, liver metastases, and leukemic blasts of patients with acute myelogenous leukemia. Since normal tissues and bone marrow of healthy human individuals do not express Hsp70 on the cell surface, Hsp70 can be considered as a tumor-selective structure in vivo. Furthermore, we demonstrate that autologous, Hsp70-positive leukemic blasts can be killed by NK cells stimulated with low doses of interleukin 2 plus recombinant Hsp70 protein.